Problem-Based Learning Model with Geogebra Support on Students' Ability to Solve Mathematical Problems - Widia Wulandari; La Misu; Salim (FKIP Universitas Halu Oleo, 2023)
The objectives of this study are to: (1) Describe the mathematical problem-solving skills of SMK Negeri 2 Kendari grade X students who are taught using the Problem Based Learning learning model with assistance from Geogebra; and (2) ascertain the impact of the Problem Based Learning learning model with assistance from Geogebra on the mathematical problem-solving skills of SMK Negeri 2 Kendari grade X students. The participants in this study were all SMK Negeri 2 Kendari grade X students enrolled in the 2022–2023 academic year. The experimental class in this study was the X TMA class, and the control class was the X TM B class. The findings demonstrated that: (1) the experimental class students' mathematical problem-solving ability, taught using the Geogebra-assisted Problem Based Learning learning model, are in the following categories: excellent, comprising up to 8 students with a percentage of 29.6%; good, comprising up to 9 students with a percentage of 33.3%; sufficient, comprising 6 students with a percentage of 22.2%; poor, comprising up to 3 students with a percentage of 11.1%; and very poor, comprising 1 student with a percentage of 3.7%. The analysis's findings lead to the conclusion that, when it comes to the two-variable linear inequality system, the experimental class's descriptive mathematical problem-solving ability, which was taught using the Problem Based Learning learning model in conjunction with Geogebra, outperformed that of the control class, which was taught using the Problem Based Learning learning model alone. The value of t hitung = 2.591 was acquired from the hypothesis testing findings. It is evident that when tcount is high, H0 is disproved. In summary, students taught using the Geogebra-assisted Problem Based Learning learning model had an average greater level of mathematical problem solving skill than students taught using the Problem Based Learning learning model.